IMPLEMENTASI KEWIRAUSAHAAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU SEKOLAH DI SD NEGERI PEKUNDEN SEMARANG - Ika Muharini Kusumaningrum; Yovitha Yuliejantiningsih; Rosalina Br. Ginting (STKIP Subang, 2023)
A school principal who has an entrepreneurial spirit means being a leader who has the ability and willingness to always innovate, work hard, have high motivation, never give up, look for and find opportunities, and influence school resources. The aim of the research is to describe and analyze the implementation of school principal entrepreneurship in improving quality at the Pekunden State Elementary School, Semarang City. The research approach used is qualitative. This type of research is a case study. Qualitative research design through data condensation, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). Data collection techniques are interviews, observation and documentation. This research uses triangulation of sources and methods. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The research results show that: 1) The school principal is proactive by inviting teachers, employees and students to have active dialogue and take a personal approach. 2) Innovative school principals by understanding the school environment around them, then not being shy about asking questions and collaborating and then having an out of the box mindset. The principal has imagination, has the power of ideas, is a creative person. 3) The principal's courageous attitude to take risks by analyzing the problems faced, then discussing them to find good alternatives and solutions. 4) The school principal works hard and never gives up by identifying various strengths, weaknesses, opportunities and threats facing the school, and being a role model in his work. 5) Motivation for achievement by school principals by analyzing programs and activities, conducting joint evaluations, analyzing student learning programs with the aim of making changes. The author suggests that school principals should further improve the implementation of entrepreneurship by being more proactive, innovative, having the courage to take risks, working hard and never giving up, and achieving motivation. Teachers are required to support and always be ready to carry out activities.